PENGARUH COVID-19 TERHADAP PENGEMBALIAN SAHAM LQ45 DI INDONESIA - isnaini Nuzula Agustin; Suryati Suryati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research attempts to investigate the effect of Confirmed Covid-19 Cases and Death Covid-19 Cases on the Stock Return by using the Exchange Rate, Oil, market to Book Ratio variables as control variables. This study use Indonesia Stock Exchange, particularly all LQ45 constituents whoch know as liquid index during the period of March 3 2020 to July 31 2021. Purposive sampling resulting 39 emitents that met the criteria. The data analysis method is Panel Regression and processed with E-views software. Under the best model selection, it was confirm that the best regression model is the Random Effect Model (REM). The results of this study confirms that Covid-19 Confirmed Cases has a significant negative effect on Stock Return, while the Covid-19 Death Cases has a significant positive effect on Stock Return. Nevertheless, impact of Death Cases is more weak than the Confirmed Cases. This findings is expected to be used as reference for investors and fund managers as the basis of decision making in capital market.